Impaired proteasome activity and neurodegeneration with brain iron accumulation in FBXO7 defect. Issue 8 (6th August 2020) - Correa‐Vela, Marta; Lupo, Vincenzo; Montpeyó, Marta; Sancho, Paula; Marcé‐Grau, Anna; Hernández‐Vara, Jorge; Darling, Alejandra; Jenkins, Alison; Fernández‐Rodríguez, Sandra; Tello, Cristina; Ramírez‐Jiménez, Laura; Pérez, Belén; et al.
Abstact: FBXO7 is implicated in the ubiquitin–proteasome system and parkin‐mediated mitophagy. FBXO7defects cause a levodopa‐responsive parkinsonian‐pyramidal syndrome(PPS). Methods: We investigated the disease molecular bases in a child with PPS and brain iron accumulation. Results: A novel homozygous c.368C>G (p.S123*) FBXO7 mutation was identified in a child with spastic paraplegia, epilepsy, cerebellar degeneration, levodopa nonresponsive parkinsonism, and brain iron deposition. Patient's fibroblasts assays demonstrated an absence of FBXO7 RNA expression leading to impaired proteasome degradation and accumulation of poly‐ubiquitinated proteins. Conclusion: This novel FBXO7 phenotype associated with impaired proteasome activity overlaps with neurodegeneration with brain iron accumulation disorders.